Ancient Rome and Pompeii - Osborne, Mary Pope and Boyce, Natalie Pope (New York Random House, 2006)
Magic Tree House Research Guides are now Magic Tree House Fact Trackers! Track the facts with Jack and Annie!? When Jack and Annie got back from their adventure in?Magic Tree House #13: Vacation Under the Volcano,?they had lots of questions. How did ancient Rome become an emipre? Where did ancient Romans go for fun? What happened to the Roman town of Pompeii? What have we learned from it? Find out the answers to these questions and more as Jack and Annie track the facts. Filled with up-to-date information, photos, illustrations, and fun tidbits from Jack and Annie, the Magic Tree House Fact Trackers are the perfect way for kids to find out more about the topics they discovered in their favorite Magic Tree House adventures.
Include Illustrations
Keywords: Rome (Empire) -- Italy--Vesuvius -- Eruption of Vesuvius (Italy : 79)